1983
DOI: 10.1017/s0025315400071198
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction, recruitment and juvenile ecology of the starfish,Asterias rubensandMarthasterias glacialis

Abstract: Reproductive cycles are described for subtidal and intertidal populations of the, starfishAsterias rubensL. and for a subtidal population of the starfishMarthasterias glacialisL. on the south-west coast of Britain. IntertidalA. rubenshad a clearly defined reproductive cycle with spring-early summer spawning. Pyloric caecum indices were inversely related to gonad indices. SubtidalA. rubenshad lower gonad indices and less seasonal variation in the pyloric caecum indices. Gonad indices ofM. glacialissuggest few a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
1
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 28 publications
5
51
1
1
Order By: Relevance
“…Marthasterias glacialis (order Forcipulata, Asteriidae) is widely distributed in Europe, from Finnmark (the northernmost county of Norway) to the Mediterranean Sea (Harmelin et al 1980;Nichols and Barker 1984;Savy 1987), being a common and emblematic species at both sides of the Gibraltar Strait, predator of bivalves and other echinoderms (Barker and Nichols 1983;Frid 1992;Guidetti 2004). Despite its abundance in the North Atlantic sublittoral habitats, it is not, in general, abundant along the Mediterranean littoral, rarely reaching densities up to 2 ind/50 m 2 (Savy 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marthasterias glacialis (order Forcipulata, Asteriidae) is widely distributed in Europe, from Finnmark (the northernmost county of Norway) to the Mediterranean Sea (Harmelin et al 1980;Nichols and Barker 1984;Savy 1987), being a common and emblematic species at both sides of the Gibraltar Strait, predator of bivalves and other echinoderms (Barker and Nichols 1983;Frid 1992;Guidetti 2004). Despite its abundance in the North Atlantic sublittoral habitats, it is not, in general, abundant along the Mediterranean littoral, rarely reaching densities up to 2 ind/50 m 2 (Savy 1987).…”
Section: Introductionmentioning
confidence: 99%
“…M. glacialis is a broadcast spawner sea star, with long dispersal capability due to a planktotrophic larva, which remains in the water column for more than 3 months, passing through several larval stages. When adhesive structures appear, the larva attaches to the substrate and the metamorphosis commences (Barker and Nichols 1983).…”
Section: Introductionmentioning
confidence: 99%
“…They were most abundant at 2 and 6 m, but also occurred sparsely at deeper levels. Barker & Nichols (1983) found that juvenile A. rubens settled in late June or early July and that small numbers of starfish continued to settle in August and September. The decrease in number of starfish in September was probably due to juvenile mortality and, to some extent, migration out of the sampling area.…”
Section: Discussionmentioning
confidence: 97%
“…Juvenile A. rubens occurred mainly at shallow sites. They feed carnivorously immediately after completion of metamorphosis (Barker & Nichols 1983). The small starfish feeds primarily on young blue mussels, Mytilus edulis L. (Mortensen 1924), which are abundant among algae and hydroids in shallow areas (Jensen & Spärck 1934).…”
Section: Discussionmentioning
confidence: 99%
“…Lorsque la ponte a lieu, de la fin mal jusqu'à juillet-août, les poids moyens de l'ovaire et ( Farmanfarmaian et al, 1958;Mauzey, 1966;Barker et Nichols, 1983). Cest ce qui semble être le cas chez le buccin, qui se nourrit peu durant cette période.…”
Section: Cycle D'alimentationunclassified